Exploring the Meaning and Role of Spirituality for Women Survivors of Intimate Partner Abuse - Fowler, Dawnovise N. (Journal of pastoral care & counseling, 2009)
Literature on trauma, coping and spirituality has introduced new questions about protective factors in the healing process for intimate partner abuse survivors (IPA). This qualitative study explores the relationship between spirituality and IPA with three focus groups of twenty-two women IPA survivors residing in a shelter. A content analysis revealed central themes that explicate the meaning and role spirituality plays for participants. Viewed as a salient dimension, spirituality provides strength, influences outcomes and assists in the regulation of behavioral responses in a positive manner in terms of participants' traumatic IPA victimization. Practice implications are discussed.